Analisis Kinetika Arrhenius Terhadap Perubahan Sifat Fisik, Kimia, Dan Kualitas Masak Beras Dengan Kombinasi Kadar Amilosa Dan Suhu Selama penyimpanan - Febriana Intan Permata Hati; Joko Nugroho Wahyu Karyadi; Nursigit Bitoro; Iqbal; Diyah Yumeina; Olly Sanny Hutabarat; Mursalim; Khaeril Anwar Junaedi (Jurnal Agritechno, 2025)
Rice is one of the staple foods consumed by Indonesians. As one of the largest rice producers, problems related to rice storage are often complained about. During storage, rice changes its cooking quality and physical and physicochemical qualities. This study aimed to analyze the kinetic behavior of cooking and the physical and physicochemical qualities of Indonesian rice varieties. Rice with different amylose contents was stored for 4 months, and the collected data from the parameters of water content, whiteness, amylose content, elongation ratio, and extrudability were analyzed using the Arrhenius equation. The combination of amylose content and temperature influences the changes in the physical, chemical, and cooking properties of rice during storage. The highest increase in water content occurred in the Ciherang variety stored at a temperature of 20 °C, namely 0.0183%/week, and the whiteness, amylose content, and elongation ratio values decreased during storage. Storage at 30 °C resulted in a greater reduction in quality, with the change in Ciherang whiteness being 0.0202/week, sintanur amylose content decreasing by 0.0105%/week, and sintanur elongation ratio decreasing by 0.0348/week at this temperature. Meanwhile, the sintanur extrudability parameter experienced an increase of 0,0174g/week at a temperature of 30 ˚C. Therefore, in general, the decline in rice quality occurs more quickly at higher temperatures.